Identificación de especies arbóreas y arbustivas para la elaboración de una propuesta de un plan de manejo en zonas de alta vulnerabilidad física y ambiental en el sector la esperanza (Transecto 3), de la parroquia El Tingo, cantón Pujilí, provincia de Cotopaxi - Murillo Gualotuña, Fabiola Inés (2013)
In the forest of La Esperanza, the accelerated process of degradation, is mainly by land use change and forest burning, factors that decrease the flow and causes the loss of water sources and hence the disappearance of native forest species sector and endemic, causing erosion of the topsoil of the soil where the forest has disappeared, being exposed to water and wind action, the same as in the study area has decreased to fifty percent of its capacity. We have identified thirty two native species and three endemic species, they have direct use value (medicine, additives, food, materials, fuel) and indirect use value (environmental services) as the regulatory and cultural species like cedro , Canelo, Rubber and Oak has a high value of timber use....